EDUKASI CEGAH ANEMIA DALAM MENINGKATKAN KONSENTRASI DAN PRESTASI PADA SISWA SMP SE KOTA TERNATE - Rahayu, Agustin; Andiani, Andiani; Surasno, Diah Merdekawati; Mansyur, Suryani; Sumiati, Tati; Lestari, Tutik (EJOIN : Jurnal Pengabdian Masyarakat, 2024)
Teenagehood is a vulnerable period for nutritional problems, especially anemia (a condition where the number of red blood cells is below standard). According to the Riskesdas (2018), the prevalence of anemia in adolescent girls is 27.2%, while in adolescent boys, it is 20.3%. Data from the North Maluku Health Office for adolescent girls in Ternate City identified a 20.11% prevalence of anemia. This Community Service activity aims to educate teenage students about the importance of avoiding anemia. Nutritional education is provided using lecture methods, conducting pre and post-tests, and measuring nutritional status. There were 36 junior high school students participating in this activity, representing each public and private junior high school in Ternate City. After the lecture, it was found that the average knowledge score of the students increased from 5.18 before the lecture to 6.26 after the lecture, indicating that nutritional education on anemia using the lecture method is quite effective in improving participants' knowledge. With increased knowledge, it is hoped that students can improve their behavior in preventing anemia by consuming iron-rich foods and regularly taking iron tablets